Creating employment through the labour-intensive public works programmes the Indonesian experience - Esmara, Hendra (1987)
To correct the employment gap and the uneven distribution of the population and labour force, the Indonesian government undertook a direct intervention program in employment creation through public works and this has become the largest nationwide effort that has been done anywhere in the world, except China. This paper will describe and assess the achievement of this employment policy over the period 1969-1984 . The programmes could be considered as successful whether in terms of the impact to the local economy (which was substantial) or in terms of direct employment creation (which activated about one-third of the underutilized labour force). In conclusion, the paper contends that relying on these labor-intensive public works programmes, which can be further expanded, cannot solve the employment problem; rather, a broader employment policy is needed.
Philippine Review of Economics and Business (formerly The Philippine Review of Business and Economics)
Includes bibliographical references (page 236)
Keywords: Labor supply -- Government policy -- Indonesia; Job creation -- Indonesia; Public works -- Indonesia; Labor policy -- Indonesia